KONTRIBUSI FLEKSIBILITAS TOGOK DAN KOORDINASI MATA TANGAN TERHADAP KEMAMPUAN DRIBBLING PEMAIN HOCKEY UNM - Dimas Afandi; Abdul Rahman; Ichsani Ichsani (Program Studi Ilmu Keolahragaan FIK UNM, 2022)
This research is a research with a regression type. The analytical method used in this research is multiple linear regression analysis technique. The purpose of this study was to determine the contribution level of stick flexibility and eye-hand coordination to the dribbling ability of UNM hockey players either partially or simultaneously. The independent variable in this study is the flexibility of the stick and eye coordination, while the dependent variable is the dribbling ability. The population in this study were all 30 UNM hockey players, while the sample was 15 male hockey players using a purposive sampling technique. The research data were obtained by providing a series of tests in the form of a stick flexibility test, an eye-hand coordination test, and a dribbling test. Based on the results of inferential statistical analysis, P = 0.000 is smaller than = 0.05. It can be concluded that the contribution of stick flexibility and eye-hand coordination has a significant effect on theability of dribbling UNM hockey players.